Identifying community-dwelling older adults' vision loss during mobility assessments: A scoping review. (April 2019) - Petty, Linda S.; Foster, Julia E. G.; Rigby, Patty
Background: Co-occurring mobility issues and vision loss are prevalent in older adults. Vision loss can cause ambulation difficulties and falls. Community-dwelling older adults frequently require mobility-aids assessment by occupational therapists. However, therapists often lack access to medical documentation on vision or training in vision assessment to ensure that clients have adequate vision for safe mobility-aid use. Purpose: This study aimed to identify screening and assessment approaches to identify functional vision loss to guide mobility-aid prescription. Method: A scoping review following Arksey and O'Malley's five stages was undertaken using Medline and CINAHL databases. A data-charting form was used for extraction of information about each article, including the population, vision diagnosis, and the methodology for vision screening. The data regarding vision loss and mobility of older adults were summarized for each article. Findings: Twenty-three papers were included in the study, describing screening questions and questionnaires or assessment tools to screen for vision loss in community settings. Implications: The various tools identified can better prepare therapists to prescribe mobility aids appropriate for seniors' level of functional vision and to refer clients for further assessment and intervention if warranted.